2014
DOI: 10.1148/radiol.13130777
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Pitch of an Organ: Quantification of Tissue Texture with Photoacoustic Spectrum Analysis

Abstract: Purpose To investigate the use of photoacoustic (PA) spectrum analysis (PASA) to identify microstructural changes corresponding to fat accumulation in mouse livers ex vivo and in situ. Materials and Methods The laboratory animal protocol for this work was approved by the university committee on use and care of animals. Six mice with normal livers and six mice with fatty livers were examined ex vivo with a PA system at 1200 nm, and nine similar pairs of mice were examined at 532 nm. To explore the feasibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
98
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 27 publications
4
98
0
Order By: Relevance
“…Photoacoustic (PA) imaging (PAI) is an imaging technique combining high optical sensitivity for discriminating the molecular contents and good ultrasonic resolution to observe microscopic architecture in biological tissues [18,19]. PAI has demonstrated the capability to assess hemoglobin and collagen contents in biological tissue [12,20]. PAI could therefore be a potential tool for the characterization of the diseased conditions in intestinal strictures.…”
Section: Introductionmentioning
confidence: 99%
“…Photoacoustic (PA) imaging (PAI) is an imaging technique combining high optical sensitivity for discriminating the molecular contents and good ultrasonic resolution to observe microscopic architecture in biological tissues [18,19]. PAI has demonstrated the capability to assess hemoglobin and collagen contents in biological tissue [12,20]. PAI could therefore be a potential tool for the characterization of the diseased conditions in intestinal strictures.…”
Section: Introductionmentioning
confidence: 99%
“…For example, by using commercially available or homefabricated piezoelectric transducers, PASA has been explored for applications in diagnosis of prostate cancer [6,12,13] and evaluation of liver conditions [7,8,14]. In these studies, PASA was performed on the tissue level, and the targeted biological tissues (e.g., small vessels, cellular groups, and lipid clusters) have features on the scale of over 100 microns.…”
Section: Introductionmentioning
confidence: 99%
“…PAT images represent the amplitude of light absorption but cannot provide details such as diagnostic information offered by the spectra of PAT beamformed data or beams, which is the delay-and-sum of all channel RF signals. Studies from other groups have revealed that the spectrum parameters from a PAT channel signal [24][25][26][27] or beam, 28,29 such as the spectral slope and 0-MHz intercept, are affected by the photoacoustic target dimension and chromospheres' concentration; [24][25][26][27][28][29] these parameters could provide valuable information for cancer characterization and classification. Furthermore, in the formation of PAT images, the spatial patterns of PAT images are affected by the manually set dynamic range and the mapping method between beam envelope and pixel values.…”
Section: Introductionmentioning
confidence: 99%